The views of family physicians on National Health Insurance in Gauteng Province, South Africa - Shane D. Murphy; Klaus von Pressentin; Shabir A. Moosa (South African Family Practice)
Background: Universal health coverage (UHC) improves national health outcomes while addressing social inequalities in access to quality healthcare services. The district health system (DHS) is critical to the success of UHC in South Africa through the National Health Insurance (NHI) scheme. Family physicians (FPs), as champions of primary care, are central to the DHS operation and implementation of NHI.